(untitled) (Journal of Architectural Design, 2022)
The article examines the types of non-stationary trade facilities, their external decorations, the impact of advertising and information boards on the urban environment and their problems. Architectural-spatial and planning solutions of nonstationary trade facilities, stylistic solutions of application in the territory of architectural facilities characteristic of different periods have been studied. The unique aspects of non-stationary trade facilities in the world and Uzbekistan, their aesthetic impact on the urban environment are analyzed